Enhancing geotechnical and environmental properties of municipal solid waste fines via biopolymer stabilization : characterization, application, and sustainability analysis - Verma, Abhay Kumar (IIT(BHU) Varanasi, 2026)
Abstract is available in the attachment.
Keywords: Civil Engineering